Challenges and Opportunities in Repurposing of Drugs: Mini Review - Sindhu, S; Murugan, S (Bangladesh Journal of Medical Science, 2020)
for treating a new clinical condition takes time and consumes a lot of investment. Therefore, there is much attention given towards repurposing of old drugs for new therapy. Majority of drugs approved by FDA for a particular treatment has found applications in the treatment of various other clinical conditions too. In other words, it can be said as ‘reusing’ of a drug. This mini review focused on the use of repurposed drugs for bacterial infections and cancer treatment. Apart from the benefits of repurposing of drugs, there are some challenges needed to be addressed. Therefore, in this review paper the use of repurposed drugs in treatment of communicable (bacterial infections) and non-communicable (cancer) diseases were discussed. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.365-371